#### Answer

y=$\frac{z-5x^2}{3}$

#### Work Step by Step

5x$^2$+3y=z
3y=z-5x$^2$
y=$\frac{z-5x^2}{3}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

y=$\frac{z-5x^2}{3}$

5x$^2$+3y=z
3y=z-5x$^2$
y=$\frac{z-5x^2}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.